Actuarial Deductions for Early Retirement - Markus Knell (Oesterreichische Nationalbank (OeNB), 2017)
The paper studies how the rates of deduction for early retirement have to be determined in PAYG systems in order to keep their budget stable. I show that the budget-neutral deductions depend on the speci_c rules of the pension system and on the choice of the discount rate which itself depends on the collective retirement behavior. For the commonly used _ction of a single individual deviating from the target retirement age the right choice is the market interest rate while for the alternative scenario of a stationary retirement distribution it is the internal rate of return of the PAYG system. In this case the necessary budget-neutral deductions are lower than under the standard approach used in the related literature. This is also true for retirement ages that uctuate randomly around a stationary distribution. Long-run shifts (e.g. increases in the average retirement age) might cause problems for the pension system but these have to be dealt with by the general pension formulas not by the deduction rates.
Keywords: H55; J1; J18; J26; 330; Pension System; Demographic Change; Financial Stability